An Ultra‐Microporous Metal–Organic Framework with Exceptional Xe Capacity. Issue 55 (16th September 2020) - Chakraborty, Debanjan; Nandi, Shyamapada; Maity, Rahul; Motkuri, Radha Kishan; Han, Kee Sung; Collins, Sean; Humble, Paul; Hayes, James C.; Woo, Tom K.; Vaidhyanathan, Ramanathan; Thallapally, Praveen K.
Abstract: Molecular confinement plays a significant effect on trapped gas and solvent molecules. A fundamental understanding of gas adsorption within the porous confinement provides information necessary to design a material with improved selectivity. In this regard, metal–organic framework (MOF) adsorbents are ideal candidate materials to study confinement effects for weakly interacting gas molecules, such as noble gases. Among the noble gases, xenon (Xe) has practical applications in the medical, automotive and aerospace industries. In this Communication, we report an ultra‐microporous nickel‐isonicotinate MOF with exceptional Xe uptake and selectivity compared to all benchmark MOF and porous organic cage materials. The selectivity arises because of the near perfect fit of the atomic Xe inside the porous confinement. Notably, at low partial pressure, the Ni–MOF interacts very strongly with Xe compared to the closely related Krypton gas (Kr) and more polarizable CO2 . Further 129 Xe NMR suggests a broad isotropic chemical shift due to the reduced motion as a result of confinement. Abstract : Noble gases : An ultra‐microporous nickel‐isonicotinate MOF with exceptional Xe uptake and selectivity is reported. The selectivity arises because of the near perfect fit of the atomic Xe inside the porous confinement. Notably, at low partial pressure, the Ni–MOF interacts very strongly with Xe compared to the closely related Krypton gas (Kr) and more polarizable CO2 (see figure).